The formation of black-hole X-ray transients - Kalogera, V (2001)
Studies of the observed characteristics of black-hole (BH) X-ray binaries can provide us with valuable information about the process of BH formation. In this paper I address some of the aspects of our current understanding of BH formation in binaries and point out some of the existing problems of current theoretical models. In particular, the measured orbital periods and donor-star properties indicate that a common-envelope phase appears to be a necessary ingredient of the evolutionary history of observed BH X-ray transients, and that it must be associated only with a modest orbital contraction. The timing of this common-envelope phase is crucial in determining the final BH masses and current evolutionary models of mass-losing massive stars place strong constraints on the possible masses for immediate BH progenitors and wind mass loss from helium stars. Last, it is interesting that, even in the absence of any source of mass loss, the highest helium-star masses predicted by current evolutionary models are still not high enough to account for the measured BH mass in V404 Cyg (> 10 Mcircle dot). An alternative for the formation of relatively massive BH may be provided by the evolutionary sequence proposed by Eggleton and Verbunt (1986), which invokes hierarchical triples as progenitors of BH X-ray binaries with low-mass companions.